Computational electrodynamics the finite-difference time-domain method - Taflove, Allen; Hagness, Susan C. (Artech House antennas and propagation library, 2005)
This extensively revised and expanded third edition of a classic bestseller offers engineers the most up-to-date and definitive resource on this critical method for solving Maxwell's equations. The method helps practitioners design antennas, wireless communications devices, high-speed digital and microwave circuits, and integrated optical devices with unsurpassed efficiency